A novel “off-on” fluorescent probe for the detection of nickel ions and its clinical application - Yi, Hua-Wei; Wang, Xian-Mo; Wu, Jia-Hao; Zhang, Chang-Li; Ding, Yi-Di (Frontiers in Bioengineering and Biotechnology, 2023)
Nickel serves as an essential micronutrient for the human body, playing a vital role in various enzymatic processes. However, excessive nickel entering the environment can cause pollution and pose serious risks to animals, plants, and human health. High concentrations of nickel ions in the human body increase the risk of various diseases, highlighting the need for accurate measurement of nickel ions levels. In this study, we designed a sequence-specific cleavage probe for nickel (II) ion called SSC-Ni. Similar to the TaqMan probe, SSC-Ni is an off-on fluorescent probe with an exceptionally low background fluorescence signal. It exhibits high detection specificity, making it highly selective for nickel ions, and the detection limit of the probe towards Ni 2+ is as low as 82 nM. The SSC-Ni probe can be utilized for convenient and cost-effective highthroughput quantitative detection of nickel ions in serum. Its user-friendly operation and affordability make it a practical solution. By addressing the lack of simple and effective nickel ion detection methods, this probe has the potential to contribute significantly to environmental monitoring and the protection of human health.